Ancient Near Eastern history and culture - Stiebing, William H. Jr. 1940-; Helft, Susan N. (Routledge, 2023)
Ancient Near Eastern History and Culture offers an historical overview of the civilizations of the ancient Near East spanning ten thousand years of history. This new edition is a comprehensive introduction to the history and culture of the Near East, from prehistory and the beginnings of farming to the fall of Achaemenid Persia. Through text, images, maps, and historical documents, readers discover the material, social, and political world of cultures from Egypt to India, allowing students to see how these intertwined cultures interacted throughout history. Now fully updated and incorporating the latest scholarship on society, religion and the economy, this book highlights the changing fortunes of these great civilizations. A special feature of this book is its many "Debating the Evidence" sections, where the reader becomes familiar with scholarly disputes concerning the interpretation of textual and archaeological evidence on a variety of topics and case studies. The fourth edition of Ancient Near Eastern History and Culture remains a crucial textbook for undergraduates and general readers studying the ancient Near East, particularly the political and social history of ancient Egypt and Mesopotamia, as well as students of archaeology and biblical studies who are working on the region"--